Monetary Policy Responses to Exogenous Perturbations: The Case of a Small Open Economy (2007-2018) - Warburton, Christopher E.S.; Jackson, Emerson Abraham (PSL Quarterly Review, 2020)
While autonomous central banks in large open economies are usually predisposed to use monetary rules to target inflation, output, and long-term interest rates, central banks in small open economies face peculiar challenges in their attempts to attain and maintain liquidity, stable prices and full employment. This paper investigates the effects of monetary policy in the case of Sierra Leone, assuming that information for rule-based monetary policy is insufficient and imprecise. We use the Bayesian model to evaluate primitive (priors), posterior enhancements and responses of key variables to exogenous perturbations based on information from 2007 to 2018. We find that the effects of disturbances that are associated with crude oil prices have a more persistent effect on national output than the dominant monetary instrument (T-Bills). The response of monetary policy to exogenous perturbations is generally weak and less persistent. Granger-causality tests reveal that internal conditions make it less likely for the central bank to robustly react to external shocks. JEL codes: E42, E 47, E50, E52